John Alexander Logan family papers - Logan, John Alexander, 1826-1886.; Logan, John A., Mrs., 1838-1923.; Logan, John Alexander, 1865-1899.; Tucker, George Edwin; Tucker, Mary Logan, 1860 or 1861-
Correspondence, legal and military papers, drafts of speeches, articles, and books, scrapbooks, maps, memorabilia, and printed matter relating chiefly to the military, political, and social history of the Civil War and postwar period. Topics include Reconstruction, the impeachment of Andrew Johnson, presidential campaigns of 1880 and 1884, Memorial Day, Grand Army of the Republic, Society of the Army of the Tennessee, World's Columbian Exposition, American Red Cross, Belgian relief work, and woman's suffrage. Principal correspondents include Clara Barton, William Jennings Bryan, George B. Cortelyou, Grenville M. Dodge, Ulysses S. Grant, Robert Todd Lincoln, John Sherman, and William T. Sherman.
Library of Congress Prints and Photographs Division.
Library of Congress Geography and Map Division.
Chiefly papers of John Alexander Logan (1826-1886), Union Army officer and U.S. senator and representative from Illinois; and of his wife, Mary Simmerson (Cunningham) Logan (1838-1923), author. Other family members represented include John Alexander Logan, Jr., George E. Tucker, and Mary Logan Tucker.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Barton, Clara, -- 1821-1912 -- Correspondence; Bryan, William Jennings, -- 1860-1925 -- Correspondence; Cortelyou, George B. -- 1862-1940 -- Correspondence; Dodge, Grenville Mellen, -- 1831-1916 -- Correspondence; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Lincoln, Robert Todd, -- 1843-1926 -- Correspondence; Johnson, Andrew, -- 1808-1875.; Sherman, John, -- 1823-1900 -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Logan family; United States. -- Army -- History -- Civil War, 1861-1865.; American Association of the Red Cross; Grand Army of the Republic; Society of the Army of the Tennessee; Elections -- United States -- 1884.; Exhibitions -- Illinois; Impeachments; Memorial Day; Reconstruction (U.S. history, 1865-1877); Veterans -- United States -- Societies, etc; Women -- Suffrage; World War, 1914-1918 -- War work -- Belgium; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Veterans; Army officers; Representatives, U.S. Congress -- Illinois; Senators, U.S. Congress -- Illinois